2016
DOI: 10.1097/md.0000000000003994
|View full text |Cite
|
Sign up to set email alerts
|

One-year adherence to oral antihyperglycemic medication and risk prediction of patient outcomes for adults with diabetes mellitus

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 16 publications
6
49
2
2
Order By: Relevance
“…The following of recommended self‐care activities, such as adhering to prescribed medication regimens, can reduce the odds of serious events or complications; however, the degree to which people perceive their susceptibility to diabetes‐related complications and detrimental events may affect the adoption and maintenance of these strategies . Similarly to earlier diabetes studies, the present study shows that people who are non‐adherent to antidiabetes therapy are at increased risk of myocardial infarction, ischaemic stroke and death . Importantly, findings advance our understanding of the impact of non‐adherence by suggesting that people with diabetes are susceptible to such outcomes within the first 5 years of initiating antidiabetes therapy.…”
Section: Discussionsupporting
confidence: 68%
“…The following of recommended self‐care activities, such as adhering to prescribed medication regimens, can reduce the odds of serious events or complications; however, the degree to which people perceive their susceptibility to diabetes‐related complications and detrimental events may affect the adoption and maintenance of these strategies . Similarly to earlier diabetes studies, the present study shows that people who are non‐adherent to antidiabetes therapy are at increased risk of myocardial infarction, ischaemic stroke and death . Importantly, findings advance our understanding of the impact of non‐adherence by suggesting that people with diabetes are susceptible to such outcomes within the first 5 years of initiating antidiabetes therapy.…”
Section: Discussionsupporting
confidence: 68%
“…30 The prevalence rate of medication non-adherence (PDC <80%) among the newly diagnosed diabetes patients was 35%, which was higher than that reported by Ho et al (21.3%) 27 but lower than that reported by Boye et al (36.9%) 28 and Huber et al (57.6%). 29 We found that there were ethnic differences in medication adherence. Indian was more likely to be medication non-adherent compared with Chinese, Malay, and others in Singapore.…”
Section: Discussionmentioning
confidence: 75%
“…27 Huber et al showed that the PDC of antihyperglycemic medication was associated with a 7% decrease in the risk of hospitalization. 29 Boye et al also provided evidence that the probability of a hospitalization and emergency room visit decreased monotonically as PDC increased. 28 Hong and Kang found that among newly diagnosed type 2 diabetes patients, patients with MPR <80% had a 1.26 times risk in hospitalization compared with patients with MPR ≥80%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Approximately 75% of that gap is attributed to poor adherence . Additionally a decrease in adherence may worsen long‐term health outcomes and consequently increase associated healthcare costs . A study conducted by Alatorre et al showed that patients initiating treatment with dulaglutide had higher adherence and persistence compared with patients initiating treatment with liraglutide or exenatide once weekly at 6‐month follow‐up.…”
Section: Introductionmentioning
confidence: 99%